How Sensitive are Low Income Families to Health Plan Prices? - Chan, David; Gruber, Jonathan (American Economic Review, 2010)
As health care reform moves forward in the United States, one common feature of virtually all proposals is to expand coverage for low income populations not through a traditional public insurance model, but rather through a “defined contribution exchange” mechanism. Under this approach, low income individuals would have a choice of a number of options for their insurance coverage. Individuals would receive a subsidy to purchase insurance that was tied to the lowest-cost plan (or some index of low-cost plans) and would pay some part of the difference if they chose a more expensive plan. This major departure from the traditional free/single-choice public payer model raises a number of important questions, but the key initial question is: How price-sensitive will lowincome consumers be in choosing across plans? While there is now a sizable literature evaluating plan choice in the context of employerprovided insurance, there are no previous studies of how these very low income populations will respond to choice in publicly financed insurance programs. In this paper, we study the plan choice of low-income enrollees in Massachusetts’ Commonwealth Care program that was established as part of the state’s health reform in April 2006. Enrollees in Commonwealth Care were given a choice of up to four Medicaid Managed The MassachuseTTs healTh Insurance experIMenT: early experIences †